Correction: Cocaine Enhances HIV-1 Replication in CD4+ T Cells by Down-Regulating MiR-125b. - Chinmay K Mantri; Jui Pandhare Dash; Jyoti Velamarti Mantri; Chandravanu Dash (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0051387.].